2008
DOI: 10.1002/app.28931
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, thermal, and viscoelastic properties of an unsaturated epoxy polyester cured with different hardeners

Abstract: The chemical modification of the structure of the unsaturated polyester obtained in poly condensation process of 1,2,3,6-tetrahydrophthalic anhydride, maleic anhydride, and ethylene glycol by well known conventional method of epoxidation with peracetic acid in mild conditions has been presented. The new material containing both epoxy groups and unsaturated double bonds in polyester chain was characterized by FTIR and 1 H NMR spectra. The prepared unsaturated epoxy polyester was suitable material for further ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Comparing the shape of the tan delta curves of the tested blends, it can be seen that the obtained materials were not homogeneous. The FWHM value of the tan delta peak is the parameter which allows to determine the homogeneity of the tested sample [45][46][47][48][49]. The FWHM values were much higher compared to the starting material.…”
Section: Dma Testmentioning
confidence: 99%
“…Comparing the shape of the tan delta curves of the tested blends, it can be seen that the obtained materials were not homogeneous. The FWHM value of the tan delta peak is the parameter which allows to determine the homogeneity of the tested sample [45][46][47][48][49]. The FWHM values were much higher compared to the starting material.…”
Section: Dma Testmentioning
confidence: 99%
“…From the micrographs of Figure (b), it observed that the ductile nature of the system increases as with the addition of 1 wt % C30B clay to the Epoxy/UP system. However, the fracture surface of Epoxy/UP/C30B become rough thus indicating the improved impact strength . The fractured surface of Epoxy/UP/ASTF system showed pull out of fibers along with a resin matrix adhering to the fiber, as shown in Figure (c).…”
Section: Resultsmentioning
confidence: 96%
“…However, the fracture surface of Epoxy/UP/C30B become rough thus indicating the improved impact strength. 46,49,89 The fractured surface of Epoxy/UP/ASTF system showed pull out of fibers along with a resin matrix adhering to the fiber, as shown in Figure 11(c). This indicates strong adhesion at the interface between the alkali-silane treated fiber and the matrix.…”
Section: Residue Characterizationmentioning
confidence: 99%
See 1 more Smart Citation